2007
DOI: 10.1093/cercor/bhm048
|View full text |Cite
|
Sign up to set email alerts
|

The Spatiotemporal Dynamics of Autobiographical Memory: Neural Correlates of Recall, Emotional Intensity, and Reliving

Abstract: We sought to map the time course of autobiographical memory retrieval, including brain regions that mediate phenomenological experiences of reliving and emotional intensity. Participants recalled personal memories to auditory word cues during event-related functional magnetic resonance imaging (fMRI). Participants pressed a button when a memory was accessed, maintained and elaborated the memory, and then gave subjective ratings of emotion and reliving. A novel fMRI approach based on timing differences capitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
292
4
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(336 citation statements)
references
References 111 publications
37
292
4
3
Order By: Relevance
“…37,38 A week's treatment with reboxetine decreased activation during recognition of positive vs negative personality-trait words in an area of the right medial frontal cortex (BA 6) similar to acute administration of reboxetine seen previously 15 (MNI coordinates x = 10, y = À10, z = 62 (current report), MNI coordinates x = 20, y = À14, z = 60 (single-dose reboxetine study)). Engagement of right medial frontal cortex (BA6) during memory retrieval has been previously reported 39 and is suggested to be greater during recognition compared to recall tasks. 40 Greater activation in right medial frontal cortex (BA 6) during retrieval of self-referentially processed personalitytrait words has also been reported.…”
Section: Reboxetine and Subsequent Recognitionmentioning
confidence: 79%
“…37,38 A week's treatment with reboxetine decreased activation during recognition of positive vs negative personality-trait words in an area of the right medial frontal cortex (BA 6) similar to acute administration of reboxetine seen previously 15 (MNI coordinates x = 10, y = À10, z = 62 (current report), MNI coordinates x = 20, y = À14, z = 60 (single-dose reboxetine study)). Engagement of right medial frontal cortex (BA6) during memory retrieval has been previously reported 39 and is suggested to be greater during recognition compared to recall tasks. 40 Greater activation in right medial frontal cortex (BA 6) during retrieval of self-referentially processed personalitytrait words has also been reported.…”
Section: Reboxetine and Subsequent Recognitionmentioning
confidence: 79%
“…Previous fMRI studies have shown that the episodic recall of life events (episodic autobiographical memory) relies on a distributed set of brain regions that includes the hippocampus, the lateral temporal cortices, the temporo-parietal junction, the medial prefrontal cortex, the precuneus, and the retrosplenial cortex (28)(29)(30). The actual contents of the memory representation are believed to be stored in the cortex, with different cortical regions dynamically linked by the hippocampus during successful episodic encoding and retrieval (28,29,(31)(32)(33). A recent neuroimaging study showed modulation of hippocampal activation by the level of rehearsal of a given autobiographical memory.…”
Section: A B Cmentioning
confidence: 99%
“…Increased activations in healthy controls were also observed in the somatosensory regions during the elaboration phase (vs. the construction phase), not evident in the patient group. In the AM literature, the somatosensory cortex is closely linked to the retrieval of somatosensory representations related to the event, the emotional intensity, and is also especially engaged during the elaboration of events (Daselaar et al 2008;Botzung et al 2010). …”
Section: Fig 4 Significant Brain Activations For the Group X Task Inmentioning
confidence: 99%